RELEVANSI KURIKULUM PENDIDIKAN ISLAM DALAM MENGHADAPI TANTANGAN ARTIFICIAL INTELLIGENCE (KECERDASAN BUATAN) - Wildayah Musyafa; Agus Pahrudin; Agus Jatmiko; Koderi; Imam Syafe’i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The advancement of Artificial Intelligence (AI) has profoundly influenced various aspects of life, including education. Islamic education, as a system of human development founded on divine values, must adapt to the changing paradigm of learning in the digital era characterized by computer and internet technologies. However, many previous studies have primarily focused on theoretical discussions about the relationship between Islam and technology or on the ethical use of AI in general contexts, without sufficiently addressing the development of a practical and relevant Islamic education curriculum for the age of artificial intelligence. This research gap indicates the need for more in-depth studies on how the Islamic education curriculum can remain relevant and aligned with technological progress while preserving its moral and spiritual foundations. The purpose of this article is to examine the relevance of the Islamic education curriculum in facing the challenges of AI and to identify opportunities and strategies for its development to ensure adaptability without losing its spiritual essence. This study employs a literature review approach by analyzing academic works published between 2020 and 2025. The findings reveal that the Islamic education curriculum must be redesigned to integrate digital skills, technological literacy, and Islamic values into every component of learning. Although AI-based learning has great potential to enhance the efficiency and effectiveness of education, it must be implemented in accordance with moral and spiritual principles to prevent dehumanization. Therefore, the contemporary Islamic education curriculum should be constructed dynamically, holistically, and futuristically, balancing digital, emotional, spiritual, and intellectual intelligences. Such curriculum reform is expected to produce a generation of Muslims who excel in technology while upholding moral integrity and transcendental awareness, enabling the ethical use of artificial intelligence for the betterment of humanity.